Barriers, enablers and outcomes reported by parents engaged with the special educational needs system in England: A qualitative study - Jennifer Saxton; Anne-Marie Burn; Xinhe Zhang; Hilary Toulmin; Jennifer Parker; Helen Casey; Jacob Matthews; Isaac Winterburn; Charlotte Tripp; Sarah Barnes; Poppy Hall; Kristine Black-Hawkins; et al. (PLoS ONE, 2025)
The UK government is currently seeking solutions to solve the ‘SEND Crisis’ in England to improve service provision and children’s outcomes. Parents play a central role in the identification of their children’s needs and support requirements and can provide valuable insight into SEND system functioning. This qualitative study explored the experiences of 22 parents in identifying their children’s needs, securing provision, and its perceived impact on the child and family. Participants’ children had a range of SEND types, including autism, learning disabilities, and mental health problems. We used one-to-one interviews in conjunction with drawn life ‘timelines’ to gain a comprehensive picture of participants’ experiences of engaging with the system over time. Thematic framework analysis identified legal protections and the advocacy efforts of parents and professionals as key enablers. Barriers included professionals’ lack of understanding about SEND (particularly autism), poor communication between services and families, and system failures. Positive outcomes parents attributed to SEND provision included health, education and social improvements, and young people gaining autonomy and independence. Perceived negative outcomes included lost educational opportunities, worsening mental health for children and their parents, and educational policies lacking long-term vision. We provide narrative portraitures which echo these themes. Our study suggests that solving the SEND crisis will require multiple actions, not only to repair fractured relationships and improve communication between professionals and families, but standardisation of key processes to reduce unfair variation in provision. The current system heavily depends on advocates within it, which can inadvertently harm parents who engage with it; children without advocates are at risk of missing out on much needed provision. Our study also demonstrates that provision can substantially improve children’s health, education and belonging in society. The government’s goal should be to ensure that this level of effective provision is accessible for all children with SEND.